(untitled) (Research, Society and Development, 2025)
Objective: To investigate the epidemiological profile and cases of hospitalizations of leprosy patients in the municipality of Pinheiro - MA from 2017 to 2024. Methodology: This is a cross-sectional, exploratory, descriptive study based on secondary data extracted from the Brazilian Unified Health System Information Technology Department (DATASUS). Results: 262 case forecasts and 81,977 leprosy hospitalizations were collected from 2017 to 2024. They were divided into variables, the first represented by gender, of which 60% of confirmed cases were male, while 57.04% of hospitalizations were female. Furthermore, 77.10% of the prognoses and 52.65% of the hospitalizations were of brown color and race. As for the cases confirmed by schooling, most were diagnosed between the 1st and 8th grade, with 38.9% being incomplete. In addition, the age range for both variables was between 15 and 59 years. By operational forms of leprosy, 76% were Multibacillary (MB) and 24% Paucibacillary. In terms of expenditure on the disease, the municipality of Pinheiro - MA spent around 65,330,035.12. Deaths from the disease decreased between 2023 and 2024, with around 52 fewer deaths. Final considerations: The study sought to investigate the epidemiology and hospitalizations for leprosy cases. However, it should be considered that some variables such as gender and age group need to be better conditioned in the national literature.